Pengetahuan tentang Zero Waste Pattern pada Mahasiswa Tata Busana PKK FPP-UNP - Suci Rahmawati; Puji Hujria Suci; Sri Zulfia Novrita; Puspaneli Puspaneli (Universitas Palangka Raya, 2024)
Textile waste is one of the 2nd largest types of waste in the world. The increasing amount of textile waste will have an impact on the environment. There has not been much development of clothing with Zero Waste techniques in Indonesia, and students as social beings also play an important role in environmental renewal through waste reduction. The purpose of this research is to understand the level of knowledge of fashion students about Zero Waste Pattern based on the level of cognitive knowledge, namely knowledge, understanding, application, analysis, synthesis and evaluation. The method in this research is descriptive quantitative with one variable, namely knowledge about Zero Waste Pattern. The research sample was 78 respondents of active Fashion Cosmetology students of the Family Welfare Education Study Program at Padang State University, class of 2019-2022. Data collection using a questionnaire with the Gutman Scale. The results showed that the knowledge of fashion students about Zero Waste Pattern was measured based on six knowledge indicators, namely: knowledge, understanding, application, analysis, synthesis and evaluation. The results showed that the Knowledge Indicator percentage was 56.41%, the Understanding Indicator percentage was 62.82% (high category), the Application Indicator percentage was 64.10%, the Analysis Indicator percentage was 57.69%, the Synthesis Indicator percentage was 80.77% and the Evaluation Indicator percentage was 74.36%. So, it can be concluded that the Fashion Management Students' Knowledge of Zero Waste Pattern is at a “high” level with an average percentage of 79.49%.